PRINCIPLES OF IMPROVING AUDIT ACTIVITY IN BUSINESS SUBJECTS - EXPERIENCE OF FOREIGN COUNTRIES (Web of Teachers: Inderscience Research, 2023)
In the article, the principles of improving audit activity in business entities - the experience of foreign countries.